Investigation and measurement of copper nanofluid impact on thermal efficiency of solar collectors - Assadi, M.K. (EDP Sciences, 2014)
This study compared the impacts of using copper nanofliud to enhance the efficiency of flat solar collectors with closed loop and under forced convection heat transfer circumstances to traditional work fluids. Various concentrations of nanoparticles in water and water/glycol, from 250ppm to 3000ppm, were examined for volume fraction impact. Results indicate that the laboratory tests were different from those under real conditions because of the high concentration of nanoparticles used in laboratory tests; however, by using nanofluid (even with low concentrations around 0.3) solar collector efficiency improved (3.2).Results have also shown that the use of copper nanofluid in ethylene glycol as the base fluid causes a significant reduction in collector efficiency, due to the increase in viscosity. However, using higher flow rates caused the heat transfer rate to rise because of increased turbulence. Â© 2014 Owned by the authors, published by EDP Sciences.